PERAN PEMBELAJARAN KONTEKSTUAL DALAM MENDORONG DEEP LEARNING DAN PENGUATAN NILAI MODERAT DI SEKOLAH DASAR: SYSTEMATIC LITERATURE REVIEW - RIZKI KHOIRIANA; ISDARYANTI, BAROKAH; WIDIARTI, NUNI; AVRILIANDA, DECKY (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the role of contextual learning in promoting deep learning and strengthening moderate values among elementary school students using a Systematic Literature Review (SLR) approach. The study is motivated by the need to enhance students' character development in the context of social diversity, as well as the persistence of surface learning practices in primary education. Data were collected by reviewing relevant scientific articles from reputable databases using keywords such as